Posttraumatic stress disorder symptoms and trauma‐informed care in higher levels of care for eating disorders. Issue 4 (31st December 2020) - Rienecke, Renee D.; Blalock, Dan V.; Duffy, Alan; Manwaring, Jamie; Le Grange, Daniel; Johnson, Craig; Mehler, Philip S.; McClanahan, Susan F.
Abstract: Objective: The purpose of the current study was to examine the prevalence and trajectory of posttraumatic stress disorder (PTSD) symptoms among patients with eating disorders (EDs) in higher level of ED care with trauma‐informed components, but without a formal evidence‐based trauma intervention. Method: Participants were 613 adults diagnosed with EDs receiving treatment at inpatient, residential, or partial hospitalization levels of care. Participants completed the PTSD Checklist‐5 (PCL‐5) at admission and discharge. Results: Over half of patients scored above the cutoff of 33 on the PCL‐5 at admission, suggestive of PTSD symptoms characteristic of a formal PTSD diagnosis. The average PCL‐5 score significantly decreased for every ED diagnostic category, and there was a significant reduction in the proportion of patients above the PCL‐5 cutoff score at discharge. PCL‐5 subscales measuring PTSD criteria B (intrusions) and C (avoidance) improved with modest effect sizes, whereas PCL‐5 subscales D (negative alterations in cognitions and mood) and E (alterations in arousal and reactivity) improved with larger effect sizes. Discussion: PTSD symptoms are prevalent among patients with EDs seeking higher levels of care. Despite not offering evidence‐based trauma‐specific interventions, PTSD symptoms decreased over the course of treatment. However, improvements cannot definitely be attributed to trauma‐informed care.